AN ANALYSIS OF COHESION IN TEXTS MADE BY ELT 7TH STUDENTS OF IKIP PGRI MADIUN: A DISCOURSE ANALYSIS - Karistiantari, Titis; Setyadi, Dwi; Purnomosasi, Lusia Kristiasih Dwi (English Teaching Journal, 2015)
The purpose of this research is to identify the cohesive devices and thematic progression which are constructed in texts made by ELT 7th Students of IKIP PGRI Madiun on Final Project of Psycholinguistic Class. This research is conducted by using Discourse Analysis and qualitative research approach. The type of this research is library research, using document as object. The technique of analysing data is Flow Model. This result of this research are: (1) The researcher finds that the cohesive devices which the most frequently used in all data is Reference with the total 122 reference, 5 substitution, 4 ellipsis, 86 conjunction, and 15 lexical cohesion. (2) The researcher finds that thematic progression in each data is different. Data one consists of 9 Linear TP and 8 Constant TP. Data two consists of 10 Linear TP, 7 Constant TP, 1 Split Theme, and 2 Split Rheme. Data Three consist of 4 Linear TP and 11 Constant TP. Data four consists of 18 Linear TP, 3 Constant TP, and 1 Split Rheme. And the last one is data five consists of 4 Linear TP, 2 Constant TP, and 2 Split Rheme.